2018
DOI: 10.7717/peerj.4296
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological dynamics ofChlamydia pecoruminfection in a longitudinal study of prime lamb production

Abstract: BackgroundChlamydia pecorum is a globally significant livestock pathogen causing pathology and production losses. The on-farm infection and serological dynamics and the relevance of existing diagnostic tools for diagnosing C. pecorum in livestock remains poorly characterized. In this study, we characterized the antigen and antibody dynamics of this pathogen in a longitudinal study of prime lamb production, utilizing the infection focused C. pecorum-specific 16S rRNA qPCR assay and serology based chlamydial Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
16
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 35 publications
9
16
4
Order By: Relevance
“…Methodological differences with previous studies prevent a direct comparison of prevalences, since in Australian lambs both serological and different molecular analyses were performed. These methodological differences, such as using flocked vs. non flocked swabs or using different molecular methods, can affect analytical sensitivity for Chlamydiaceae detection [ 23 ], further complicating prevalence comparison. Apart from the methodological aspects, possible differences in sample prevalence may respond to different epidemiological situations.…”
Section: Discussionmentioning
confidence: 99%
“…Methodological differences with previous studies prevent a direct comparison of prevalences, since in Australian lambs both serological and different molecular analyses were performed. These methodological differences, such as using flocked vs. non flocked swabs or using different molecular methods, can affect analytical sensitivity for Chlamydiaceae detection [ 23 ], further complicating prevalence comparison. Apart from the methodological aspects, possible differences in sample prevalence may respond to different epidemiological situations.…”
Section: Discussionmentioning
confidence: 99%
“…The swabs (n = 149) were processed by vortexing and heating to 95°C, followed by DNA extraction using a QIAmp DNA kit (Qiagen, Doncaster, Australia) . The use and testing of these swabs was considered and approved for exemption by the University of The Sunshine Coast (USC) Animal Ethics Committee (AN/E/14/01).…”
Section: Methodsmentioning
confidence: 99%
“…The intestinal site appears to be a natural habitat for infection of chlamydiae infecting mammalian and avian hosts, wherein studies have reported long-term GIT infections with continual shedding of the pathogen in the feces (Meyer and Eddie, 1933; York and Baker, 1951; Yang et al, 2014). This is particularly important because GIT infections associated with fecal shedding in flocks and herds appear to be the precursor to abortion, encephalitis, polyarthritis, conjunctivitis, and pneumonia in ruminants (Campos-Hernández et al, 2014; Hoffmann et al, 2015; Walker et al, 2016; Bommana et al, 2018). Ruminal and small animal models also suggest that neither the host immune system nor the use of antimicrobials is successful in clearing chlamydiae from the gut (Yeruva et al, 2013; Rank and Yeruva, 2014), due to the establishment of an antibiotic-protected reservoir in the GIT and down regulatory mechanisms further inhibiting the adaptive immune response from resolving GIT infections (Igietseme et al, 2001).…”
Section: Future Directions and Concluding Remarksmentioning
confidence: 99%